Tales of a Fourth Grade Nothing - Blume, Judy (Random House Children book, 1995)
And now, Puffin Books honors forty years of the book that started it all, Tales of a Fourth Grade Nothing, with a special edition--featuring a new introduction from Judy--to celebrate this perennial favorite.
Keywords: Juvenile literature-Fiction